A systematic review of human-to-human transmission of measles vaccine virus. Issue 23 (17th May 2016) - Greenwood, Kathryn P.; Hafiz, Radwan; Ware, Robert S.; Lambert, Stephen B.
Highlights: There is no documented evidence of measles vaccine virus transmission. On rare occasions vaccinees present with vaccine-associated measles. Successful vaccination strategies have enabled genotypic analysis of fewer cases. Abstract: Measles is one of the most contagious human diseases. Administration of the live attenuated measles vaccine has substantially reduced childhood mortality and morbidity since its licensure in 1963. The live but attenuated form of the vaccine describes a virus poorly adapted to replicating in human tissue, but with a replication yield sufficient to elicit an immune response for long-term protection. Given the high transmissibility of the wild-type virus and that transmission of other live vaccine viruses has been documented, we conducted a systematic review to establish if there is any evidence of human-to-human transmission of the live attenuated measles vaccine virus. We reviewed 773 articles for genotypic confirmation of a vaccine virus transmitted from a recently vaccinated individual to a susceptible close contact. No evidence of human-to-human transmission of the measles vaccine virus has been reported amongst the thousands of clinical samples genotyped during outbreaks or endemic transmission and individual case studies worldwide.